The clinical value of serum soluble interleukin-2 receptor in pulmonary sarcoidosis - Ogata-Suetsugu, Saiko; Hamada, Naoki; Takayama, Koichi; Tsubouchi, Kazuya; Arimura-Omori, Masako; Nakanishi, Yoichi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Background: Sarcoidosis is a multi-system granulomatous disease in which T-helper type 1 cytokines play a key role. We evaluated the clinical value of serum soluble interleukin-2 receptor (sIL-2R) as a marker of disease activity and prognosis in sarcoidosis. Methods: This study included 67 patients who were newly diagnosed with sarcoidosis from 2006 to 2012 at our department. The clinical and follow-up data were retrospectively collected from their medical records. Results: The mean (±SD) age of the patients was 53.9±15.4 years; 41 patients were women and were significantly older than men. Serum angiotensin-converting enzyme had a mean value of 15.3±6.1 U/L and a positive rate of 10.4%. Serum sIL-2R had mean level of 818.8±453.1 U/mL and a positive rate of 45.9%. Moreover, the sIL-2R level of patients who had lung parenchymal lesions was significantly higher than that of patients who had no lung parenchymal lesions. Fifty-two patients who had no medications were followed up at our hospital for a median period of 37 months (range, 0–107 months). Patients who demonstrated chest imaging evidence of exacerbation (n = 8) tended to have higher sIL-2R levels than those who remained stable. Conclusion: Serum sIL-2R may have a role as a diagnostic and prognostic marker in pulmonary sarcoidosis.